Fluid Biomarkers in Clinical Trials of Alzheimer’s Disease Therapeutics - Ritter, Aaron; Cummings, Jeffrey (Frontiers in Neurology, 2015)
With the demographic shift of the global population toward longer life expectancy, the number of people living with Alzheimer’s disease (AD) has rapidly expanded and is projected to triple by the year 2050. Current treatments provide symptomatic relief but do not affect the underlying pathology of the disease. Therapies that prevent or slow the progression of the disease are urgently needed to avoid this growing public health emergency. Insights gained from decades of research have begun to unlock the pathophysiology of this complex disease and have provided targets for disease-modifying therapies. In the last decade, few therapeutic agents designed to modify the underlying disease process have progressed to clinical trials and none have been brought to market. With the focus on disease modification, biomarkers promise to play an increasingly important role in clinical trials. Six biomarkers have now been included in diagnostic criteria for AD and are regularly incorporated into clinical trials. Three biomarkers are neuroimaging measures – hippocampal atrophy measured by magnetic resonance imaging (MRI), amyloid uptake as measured by Pittsburg compound B positron emission tomography (PiB-PET), and decreased fluorodeoxyglucose (18F) uptake as measured by PET (FDG-PET) – and three are sampled from fluid sources – cerebrospinal fluid levels of amyloid β42 (Aβ42), total tau, and phosphorylated tau. Fluid biomarkers are important because they can provide information regarding the underlying biochemical processes that are occurring in the brain. The purpose of this paper is to review the literature regarding the existing and emerging fluid biomarkers and to examine how fluid biomarkers have been incorporated into clinical trials.